Studi Pengetahuan dan Penggunaan terhadap Obat Tradisional pada Masyarakat di Kelurahan Beji - Setiaji Wisnu Wardana; Siti Khoiriyah (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2025)
Traditional medicine is a concoction that is used for hereditary treatment. One type of traditional medicine that is widely used is herbal medicine. This study was conducted with the aim of a preliminary study to determine the level of knowledge and use of traditional medicine in the community. The sampling technique in this study was carried out by purpose sampling and calculated using the Slovin formula. The method of data collection in this study used a questionnaire given to the elderly community in RW 13, Beji Village, East Ungaran District. Data obtained from 28 respondents and the results showed that the level of community knowledge of traditional medicine in RW.13, Beji Village, East Ungaran District, as a whole, the community knows about traditional medicine, which is 75%, but the majority of the community does not know about the classification of traditional medicine (39.29%). While the level of use of traditional medicine, the majority of people rarely consume it.